Zoning System In Education Application In The City Of Pasuruan, East Java: Zoning System, Access and Quality Improvement, the City of Pasuruan. - Daryono Daryono (EDUTEC : Journal of Education And Technology, 2021)
This paper examines the application of the zonation system in the City of Pasuruan. Based on preliminary observations of the zoning system in Pasuruan through the Education and Culture Office of Pasuruan City, it showed that; (a) the zoning system has been implemented in Pasuruan City, (b) there are written regulations regarding the implementation of zoning system policies in Pasuruan City, (c) there are technical guidelines regarding zoning system policies in Pasuruan City, (d) there is socialization regarding the requirements and flow of registration admission of new students (PPDB), (e) there is a schedule and time for registration, (f) there is a score for PPDB supporting values, (g) there is a school capacity, and (h) there is a division of zoning area designations. The purpose of this study was to explain parents' perceptions, equal access and improve the quality of education. The research method in this study used field research methods, namely direct observation of the research subject (parents of students) and combined with literature study. The research approach wass a qualitative approach. The qualitative research procedure produced descriptive data in the form of sentences or writings from other researchers as reinforcement of explanations in the articles and field data that the authors refer to. From the results of the study, most of the parents of students assumed that the zoning system policy was a process of admitting new students based on distance, namely the distance between the house to the school. The positive impact was that parents of students did not bother thinking children's transportation costs. The students’ parents found that it was easier to monitor their children's interactions at school and in their neighborhood.Keywords: Sistem Zonasi, Akses dan Peningkatan Mutu Pendidikan, Kota Pasuruan.